The poetics of planetary theatre: image and bricolage - Muftic, Sanjin (Department of Drama, 2020)
Images are all around us. They serve as a tool of communication, whether transmitted in words, sound or in visual media. An image may simultaneously be a thing placed in front of us and a thing that we create in our minds – a fragment that fleetingly captures our attention and is difficult to articulate. To describe images is to undo them: they are too unstable, fluid, and personal to each of us, yet we constantly exchange them. In this sense, images become migrants as they travel through time, cultures and media; repeating, re-occurring, re-mixing and carrying the baggage of their contexts in their journeys. They contribute to shaping identities and culture in a global intermedial space saturated by media exposure. The central question of this study is how images work to make theatre. I place myself within the postdramatic and intercultural theatre context and consider how one of the tasks of the theatre-maker is to construct and shape images into a performance. Through a focus on several theatre productions, I investigate the features of theatrical images and highlight their usefulness within both the devising and performance stages of theatre-making. In doing so, I develop a poetics to establish an image-driven dramaturgy from rehearsal to performance. This poetics places the body in an intermedial space which constructs itself through the exchange and juxtaposition of images from across the planet. My investigation is guided by two interwoven theories. The first is that of Gayatri Chakravorty Spivak’s (2003a) concept of the planetary, which asserts the necessity of recognizing diverse experiences and perceptions on the planet in order to redefine who we see as the “other”. I utilize her approach by juxtaposing fragments in order to defamiliarize theatrical images. Through the use of fragments, the second theory of bricolage is informed by, amongst others, Claude Lévi-Strauss (1966). I thus seek to identify myself as a bricoleur; someone whose art-making poetics is dependent on using pre-existing material through sampling and montage. These poetics seek to capture my own experience as a migrant, who sees the planet as a rhizome of images and their associations. My project makes the claim that a poetics of the planetary (dramaturgy) is found through the exchange of images drawn from those involved in the creation of an intermedial theatrical event.